The Influence Of Social Media On Business Success - Julianis Clara Debora (SEAN Institute, 2023)
Currently, the rapid development of technology is marked by the large number of people using technology to help their work. Most of the use of the internet by entrepreneurs is used for promotional media via social media. With marketing methods that use sophisticated information and communication technology via social media, many entrepreneurs use it to promote their products. The purpose of this study was to determine the extent to which the influence of social media on business success, especially for culinary traders in Medan Johor District. This study uses a quantitative approach with a survey technique of 76 culinary traders who actively use social media to promote their business. The variables studied include the frequency of using social media, the type of content posted, and interactions with consumers. There is a significant relationship between the intensity of using social media and increased sales. Business actors who regularly update content and interact with their consumers through social media tend to have an increase in sales of 25% compared to those who are less active. In addition, the type of content that is relevant and interesting also influences consumer loyalty. Social media has an important role in increasing business success, especially in terms of marketing and promotion. Using the right strategy on social media can increase sales and consumer loyalty. Business actors who regularly update content and interact with their consumers through social media tend to have an increase in sales of 25% compared to those who are less active. In addition, the type of content that is relevant and interesting also influences consumer loyalty. Social media has an important role in increasing business success, especially in terms of marketing and promotion. Using the right strategy on social media can increase sales and consumer loyalty. Business actors who regularly update content and interact with their consumers through social media tend to have an increase in sales of 25% compared to those who are less active. In addition, the type of content that is relevant and interesting also influences consumer loyalty. Social media has an important role in increasing business success, especially in terms of marketing and promotion. Using the right strategy on social media can increase sales and consumer loyalty.